Sense of Place: Narrating Emotional Experiences of Malaysian Borneo through Western Travel Blogs - Wong, Siao Fui; Balvinder Kaur Kler; Bamini KPD Balakrishnan (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Tourists’ sense of place or destination attachment could play an important role in destination branding. Yet, sense of place literature focuses on residents as the concept originates from a long-term residence in one place. This study explores the role of destination attachment based on tourist experience for branding based on a case study in Malaysian Borneo. A qualitative content analysis using QCAmap of 34 blogs extracted 116 blogposts with narratives containing emotional sentiments from international tourists. Findings uncovered six important attributes: namely nature, adventure, environment, culture, conservation, and education associated with destination attachment. Findings show that these attributes are interconnected as the main attribute, nature, produces other attributes. A tourists’ sense of place model for destination attachment is proposed to understand how tourists develop attachment to a place.